2008
DOI: 10.1038/leu.2008.280
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α therapy in bcr-abl-negative myeloproliferative neoplasms

Abstract: Interferon (IFN) was the first cytokine discovered 50 years ago, with a wide range of biological properties, including immunomodulatory, proapoptotic and antiangiogenic activities, that rapidly raised interest in its therapeutic use in malignancies. IFN-receptor characterization was also pivotal in the discovery of the JAK/STAT signaling pathway. Among the large IFN family, mainly one of the type I IFN, IFN-a2, is used in therapy. Many clinical trials have shown remarkable efficacy of IFN-a in bcr-abl-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
4
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 93 publications
2
126
4
9
Order By: Relevance
“…The median spleen sizes in centimeters below the left costal margin were 7.0 cm (range 0.0-24.0 cm) before treatment, and 0 cm (range 0.0-20.0 cm) at last follow-up (Table 1). Our results are thus in sharp contrast with those reported in the literature by Kiladjian et al 1 Bone marrow follow-up studies were possible in nine of the 13 patients, and were carried out a median of 2.3 years after the start of the rIFNa-2b therapy (range 1.2-5.0 years). The median duration of interferon treatment was 3.0 years (range 0.17-13.4 years).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…The median spleen sizes in centimeters below the left costal margin were 7.0 cm (range 0.0-24.0 cm) before treatment, and 0 cm (range 0.0-20.0 cm) at last follow-up (Table 1). Our results are thus in sharp contrast with those reported in the literature by Kiladjian et al 1 Bone marrow follow-up studies were possible in nine of the 13 patients, and were carried out a median of 2.3 years after the start of the rIFNa-2b therapy (range 1.2-5.0 years). The median duration of interferon treatment was 3.0 years (range 0.17-13.4 years).…”
contrasting
confidence: 56%
“…The use of interferon is based on its effects on megakaryopoiesis, which include decreasing megakaryocyte density and size, 2 inhibiting thrombopoietin-induced signaling, 3 suppressing the expression of transcription factors 4 and reducing levels of platelet-derived growth factor, 5 all of which play a major role in the pathogenesis of myelofibrosis. 1 The diagnosis of PM was established clinically, hematologically and by bone-marrow trephine biopsy, consistent with published criteria. [4][5][6] Pretreatment evaluation included history, physical examination, complete blood cell count and differential CD34 count, BCR-ABL and JAK2 V617F allele burden determinations, serum chemistries and thyroid function tests.…”
mentioning
confidence: 99%
“…It is now well established that IFN-a can control erythrocytosis or thrombocytosis in the majority patients with PV or ET (usual dose is 3 million units SC three times-a-week) [118]. A similar degree of benefit is appreciated in terms of reduction in spleen size or relief from pruritus.…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 98%
“…Since 1987, several studies have suggested that interferons (alpha or beta that are either pegylated or not) may be beneficial in the treatment of myelofibrosis (Parmeggiani et al, 1987;Kiladjian et al, 2008a). Given the efficacy of pegylated interferon a-2a (Peg-IFN a-2a) on biological and molecular parameters in polycythemia vera (PV) patients (Kiladjian et al, 2008b), we undertook a multicentre retrospective study in order to evaluate the impact of this treatment on the clinical and biological parameters inherent to myelofibrosis.…”
Section: Peg-ifn-a-2a Therapy In Patients With Myelofibrosis a Studymentioning
confidence: 99%